Recensiones - F. J. I.; Tallein, Carlos; Montes, Segundo; J. M. G.; López Vallecillos , I. (ECA: Estudios Centroamericanos, 1976)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 31, No. 334, 1976: 407-411.